Building a Professional Counsellor Identity: The Mediating Role of Competence in the Relationship between Mind Skills and Professional Identity among School Counsellors - Nurbatin, Suci; Sigit Sanyata (KONSELOR, 2025)
This research examines competency as a mediator between mind skills and professional identity among school counsellors in North Kalimantan Province. This research employed a quantitative-correlational approach. The research respondents were 101 school counsellors. Data collection used the Mind Skills psychological scale (α = 0.951), Competence (α = 0.951), and Professional Identity (α = 0.961), with very high reliability. The Sobel Test was 7.155 with a standard error of 0.091 and a p-value (sig) = 0.000 (<0.05). This shows that competence mediates between mind skills and professional identity.